Islændingesagaer og erindring - Hermann, Pernille (K&K - Kultur og Klasse, 2014)
Based on the assumption that the longstanding discussion about history/fiction has exhausted itself, this article suggests an alternative approach to the sagas of Icelanders. It approaches the sagas from a memory perspective and illustrates how two concepts of memory: cultural memory and artificial memory, provide us with useful methodological tools for opening new dimensions of saga narratives.